Significance of the determination of doppler sonography haemodynamic indices for the assessment of distal perfusion in patients with critical ischemia of lower limbs - Čizmić Milica; Kronja Goran; Ajdinović Boris; Pucar Dragan (Vojnosanitetski Pregled)
Background/Aim: The perfusion of tissue, especially the muscles of the lower limbs (LL), implies the blood flow that carries enough nutrition, energy materials and oxygen. The aim of this study was to determine whether the decreased Doppler sonography parameters, resistance index (RI), and pulsatility index (PI) were significant as indicators of irreversible ischemia of LL. Methods. In 40 patients (mean age 66±14.9 years, 21% women and 79% men) with the signs of critical ischemia of LL, Lariche-Fontaine class III and IV, we performed contrast angiography of the LL arteries, and perfusion scintigraphy of LL using, thallium-201, while we performed Doppler sonography to determine resistance index (RI), as well as pulsatility index (PI). After that, all the patients were treated with vasodilatation using Bergmann's solution within a 10-day period. Following that, all the patients underwent the determination of haemodynamic indices RI and PI applying the methods of Doppler sonography. The obtained values of RI and PI indices revealed no clinical recovery which suggested the irreversibility of critical ischemia (unsuccessful therapy in 100% of the patients), and clinical recovery which suggested the reversibility of the disease (unsuccessful therapy in 80% of the patients). Results. The obtained values of PI = 0-0.3 and RI = 0-0.25 for the examined LL arteries were the indicators of irreversible ischemia. A significant correlation between the values of RI in the distal parts of a. tibialis anterior and posterior was proved, as well as between the decreased perfusion of LL determined by tallium-201 (p < 0.05, r = 0.43), and a tibialis anterior (p = 0.05, r = 0.38). There was, however, no statistically significant correlation between the angiographic values and perfusion scintigraphy of LL. Conclusion. The obtained values of haemodynamic RI and PI indices should be a novel approach for introducing a new criteria for the assessment of reversible and irreversible critical ischemia of LL using the method of Doppler.